Bridging Deep Tech Ecosystems and Global New Industrial Policies: A Regional Perspective - Nuria Esther Laguna Molina; Oihana Basilio Ruiz de Apodaca (Revista de Economía Mundial)
This paper aims to analyse the dynamic relationships between prices, wages and private consumption for a sample of the 12 initial Economic and Monetary Union (EMU) members for the period 1999-2019. To do so, we adopt a novel approach based on panel-VAR model that allows us to perform a multivariate Granger causality analysis between the variables mentioned within a complex information system which also includes labour market and economic cycle variables. In a second stage, we complete this analysis with the application of the iterative PC algorithm that makes it possible to interpret the results of the model in the lines of graphic theory and causal graphs methods. The results obtained reveal a causal relationship from prices to wages, supporting the wage indexation hypothesis for the whole sample. On the contrary, we do not find evidence of wages causing any increase of prices, which enables us to disregard the wage-inflation hypothesis. Additionally, the approach adopted enables country-specific analyses, which are essential for understanding the specificities of each economy. In this regard, we find that Ireland is the only country where private consumption appears to exert pressure on prices. Meanwhile, Mediterranean economies like Spain and Greece seem to follow a debt-led model where private consumption drives wage levels.